Conceptual model for capability planning in a military context – A systems thinking approach. Issue 5 (30th May 2022) - Koivisto, Jouni; Ritala, Risto; Vilkko, Matti
Abstract: During recent decades, planning defense systems have evolved into capability‐based planning (CBP) processes. This paper seeks to answer two questions: firstly, how to express a complex, real‐world capability requirement; and secondly, how to assess if a system with interacting elements fulfills this requirement. We propose that both a capability need and the solution fulfilling it are expressed with a consistent set of models in a traceable manner. The models integrate current capability models, specific to planning level and capability viewpoint, with systems thinking approach. Our conceptual model defines the defense system in its environment, our data model defines and organizes the CBP terms, and our class diagram defines the CBP planning elements. We illustrate the approach by giving an example of capability parametrization and compare it both with the DODAF capability view and with the generic CBP process. Our data model describes how capabilities are degraded in action and extends the approach toward capability dynamics. The quantitative capability definition aims to support efforts to solve for real world interacting subsystems that combined implement the required capability.